2007
DOI: 10.1016/j.wasman.2006.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Optimal bulking agent particle size and usage for heat retention and disinfection in domestic wastewater sludge composting

Abstract: Composting of two types of sludge produced in wastewater treatment plants, raw sludge (RS) and anaerobically digested sludge (ADS), has been systematically studied by means of the experimental design technique. The results have been analyzed using a full factorial experimental design in order to determine the optimal conditions for composting such sludges in terms of bulking agent particle size and bulking agent:sludge volumetric ratio, two of the key parameters to ensure an optimal performance of the composti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…Michel et al (2004) and Hao et al (2004) found a lower decomposition of the compost substrate when using bulking materials rich in lignin (woodchip and sawdust) compared to composting with straw, which had a lower lignin content. In this study, the higher degradability of the sawdust may have been associated with its larger surface area-to-mass ratio, and also with the fact that the small bulking agent particles create a real porous structure and a homogeneous porous size distribution inside the material that acts as an efficient oxygen diffuser (Gea et al, 2007). However, an experiment with pig manure alone or pig manure with an inert bulking agent was not performed in this study, so it was not possible to evaluate the degradability of the bulking agents alone.…”
Section: Carbon and Nitrogen Balance During Compostingmentioning
confidence: 90%
See 2 more Smart Citations
“…Michel et al (2004) and Hao et al (2004) found a lower decomposition of the compost substrate when using bulking materials rich in lignin (woodchip and sawdust) compared to composting with straw, which had a lower lignin content. In this study, the higher degradability of the sawdust may have been associated with its larger surface area-to-mass ratio, and also with the fact that the small bulking agent particles create a real porous structure and a homogeneous porous size distribution inside the material that acts as an efficient oxygen diffuser (Gea et al, 2007). However, an experiment with pig manure alone or pig manure with an inert bulking agent was not performed in this study, so it was not possible to evaluate the degradability of the bulking agents alone.…”
Section: Carbon and Nitrogen Balance During Compostingmentioning
confidence: 90%
“…Therefore, the addition of a bulking agent is necessary to compost the separated solid fraction of pig manure (Nolan et al, 2011). A bulking agent is the material that adjusts the C/N ratio, provides optimum free air space (FAS), and regulates the water content of the waste to be composted (Gea et al, 2007;Kato and Miura, 2008;Iqbal et al, 2010;Jolanun and Towprayoon, 2010;Doublet et al, 2011), which are usually fibrous with carbonaceous material (Iqbal et al, 2010). The bulking agent represents a large proportion of the composting mixture as a source of carbon and energy for micro-organisms (Adhikari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eftoda and McCartney (2004) studied BA requirements to optimize the free air space (FAS) value of sludge composted with wood chips. Gea et al (2007) are among the few who studied the individual effect of BA particle size distribution and mass ratio on sludge compost behaviour (O 2 uptake, consolidation, airflow patterns), but the interaction between MC and BA particle size distribution was not investigated. Therefore, the objective of this project was to study the impact and interaction of initial MC and BA particle size distribution on compost material biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies also laid out the effect of adding bulking agents in which to adjust the MC, N-content, C/N ratio, and void spaces between particles in the past, since most waste materials such as sewage sludge, food waste and animal manure have too low C/N ratios and too high MC for efficient composting [6][7][8][9]. Generally, modification of physical properties of composting feed-stock may resulted from different bulking agents as well as change the biodegradation kinetics and composting performance [7,8,10].…”
Section: Introductionmentioning
confidence: 99%